Rate of recurrent vestibular schwannoma after total removal via different surgical approaches - Raja Lope Ahmad, Raja Ahmad Al'konee; Sivalingam, Shailendar; Topsakal, Vedat; Russo, Alessandra; Taibah, Abdelkader; Sanna, Mario (Annals Publishing Company, 2012)
Objective: The objective of this study was to assess the differences in the recurrence rates of vestibular schwannoma (VS) after total tumor removal through enlarged translabyrinthine (ETLA), retrosigmoid (RS) and middle cranial fossa (MCF) approaches. Our results were compared with previously published data, and literature reviews were done to identify the possible causes for the recurrence of VS. Methods: We performed a retrospective analysis of 2,400 cases of VS that underwent removal at the Gruppo Otologico, Piacenza, Italy from 1983 until 2010. The minimum postoperative follow-up was 12 months. We also reviewed the previously published data on recurrence rates of VS after ETLA, RS, and MCF approaches. Results: Total tumor removal was achieved in 2,252 cases (93.8%). The recurrence rate was 0.05% for ETL approach, 0.7% for RS approach, and 1.8% for the MCF approach. Literature reviews of 3 previously published case series utilizing the translabyrinthine approach showed that none of the primary tumors were less than 2.0 cm in size. Recurrences were seen between 1 and 13 years after the initial surgery. Conclusion: The rate of VS recurrence after total removal is exceptionally low in experienced hands. Undetected microscopic deposits left on crucial points such as the facial nerve, the preserved cochlea nerve or the fundus of the internal auditory canal could be possible causes for the recurrence. A definite advantage of an ETL approach is the excellent internal auditory canal exposure, resulting in an extremely low rate of VS recurrence. The patients should be followed up to 15 years with gadolinium-enhanced magnetic resonance imaging (with fat suppression sequence in ETL approach cases). Recurrent VS may exhibit a faster growth rate as than primary VS. Key Words:middle cranial fossa approach, recurrence, retrosigmoid approach, translabyrinthine approach, vestibular schwannoma